1990
DOI: 10.1164/ajrccm/142.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bronchoalveolar Cell and Mediator Response to Isocapnic Hyperpnea in Asthma

Abstract: The purpose of this study was to test the hypothesis that mediators and cells associated with bronchoconstriction or inflammation are locally synthesized and/or released in the airways of asthmatic subjects in response to isocapnic hyperpnea (ISH). Seven atopic, mildly asthmatic subjects were studied. Baseline measurements were reported previously and included forced expiratory volumes, flow rates, bronchoalveolar lavage (BAL), and methacholine reactivity. Approximately 1 yr later, spirometry and BAL were repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 13 publications
3
44
0
1
Order By: Relevance
“…Surprisingly, there was no difference in BALF protein concentrations from control, dry air and NaCl exposed segments, 5 min after challenge. BALF recovered from asthmatic subjects after 5 min of isocapnic hyperventilation revealed similar results: although epithelial cell numbers were elevated in BALF, BALF total protein was not increased after challenge [12]. Either BALF total protein is too insensitive to be used as a marker of dry air-induced airway injury, or airway drying transiently alters epithelial cell adhesion, and increases the probability that these cells would be washed out during lavage.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Surprisingly, there was no difference in BALF protein concentrations from control, dry air and NaCl exposed segments, 5 min after challenge. BALF recovered from asthmatic subjects after 5 min of isocapnic hyperventilation revealed similar results: although epithelial cell numbers were elevated in BALF, BALF total protein was not increased after challenge [12]. Either BALF total protein is too insensitive to be used as a marker of dry air-induced airway injury, or airway drying transiently alters epithelial cell adhesion, and increases the probability that these cells would be washed out during lavage.…”
Section: Discussionmentioning
confidence: 76%
“…Although mediator release has been implicated in AIB [12,19,21,33] and HIB [34][35][36], the role of biochemical mediators in the initiation of these responses remains controversial. The protection provided by antihistamines [19,34,35], mast cell "stabilizers" [36], cyclooxygenase inhibitors [11,19], and leukotriene receptor antagonists [21,37,38] suggest at least a partial role for these mediators in the development of AIB and HIB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different investigators have not found increased cysLT-levels in urine or BAL after exercise in adults [33±35] whereas other investigators have reported increased urinary leukotriene E 4 levels in asthmatic children after exer-cise and in adults [36]. In accordance with this, PLISS et al [1] described increased cysLT-levels in BAL fluid after hyperventilation. There are only very few and preliminary data about cysLTlevels in sputum samples from asthmatics [36].…”
Section: Discussionmentioning
confidence: 85%
“…11 showed such a high degree of variability under placebo conditions that it was impossible to draw any conclusion about the potential effects of zafirlukast. In previous studies with cysLT 1 -receptor antagonists and 5-lipoxygenase inhibitors it has been shown that 30±40% of the subjects did not show any beneficial effect on protection against bronchoconstriction induced by exercise or cold air [4,5]. In a more recent study FISCHER et al [28] analysed the protective effect of a 5-lipoxygenase inhibitor against cold air challenge.…”
Section: Discussionmentioning
confidence: 99%